Lipopolysaccharide, Identified Using an Antibody and by PAS Staining, Is Associated With Corpora amylacea and White Matter Injury in Alzheimer's Disease and Aging Brain - Zhan, Xinhua; Hakoupian, Marisa; Jin, Lee-Way; Sharp, Frank R. (Frontiers in Aging Neuroscience, 2021)
Corpora amylacea (CA) increase in number and size with aging. Their origins and functions remain unknown. Previously we found Alzheimer’s disease (AD) brains have more CA in the periventricular white matter (PVWM) compared to aging controls. In addition, CA are associated with neurodegeneration as indicated by colocalization of degraded myelin basic protein (dMBP) with periodic acid-Schiff (PAS), a CA marker. We also found that bacterial lipopolysaccharide is present in aging brains, with more LPS in AD compared to controls. PAS staining is used to identify CA by virtue of their high polysaccharide content. Despite the growing knowledge of CA as a contributor of AD pathology, the molecules that contribute to the polysaccharides in CA are not known. Notably, LPS is an important cell-surface polysaccharide found in all Gram-negative bacteria. However, it is unknown whether PAS could detect LPS, whether the LPS found in aging brains contributes to the polysaccharide found in CA, and whether LPS associates with myelin injury. In this study, we found that aging brains had a myelin deficit zone (MDZ) adjacent to the ventricles in PVWM. The MDZ contained vesicles, most of which were CA. LPS and dMBP levels were higher in AD than control brains. LPS was colocalized with dMBP in the vesicles/CA, linking white matter injury with a bacterial pro-inflammatory molecule. The vesicles also contained oxidized fibers, C-reactive protein, NG2 and GALC, markers of oligodendrocyte precursor cells (OPCs) and oligodendrocyte cells (OLs), respectively. The vesicles/CA were surrounded by dense astrocyte processes in control and AD brains. LPS was co-localized with CA by double staining of PAS with LPS in aging brains. The relationship of LPS with PAS staining was confirmed by PAS staining of purified LPS on nitrocellulose membranes. These findings reveal LPS is one of the polysaccharides found in CA which can be stained with PAS. In addition, vesicles/CA are associated with oxidized, damaged myelin. The LPS in these vesicles/CA may have contributed to this oxidative myelin damage, and may have contributed to oxidative stress to OPCs and OLs which could impair the ability to repair damaged myelin in AD and control brains.